Sundaes & splits : delicious recipes for ice cream treats - Miles, Hannah (London, United Kingdom : Ryland Peters & Small, 2010)
Presents a sundae to suit various tastes, whether it's a fresh and fruity concoction or a rich dessert laden with chocolate sauce and nuts. This title offers recipes for a Peach Melba Sundae, a Hawaiian Sundae bursting with tropical flavours, a Chocolate Brownie Sundae and a Panna Cotta Sundae garnished with raspberries and gold leaf.
Indulgent treats for everyone -- Basic recipes -- Fruity sundaes -- Indulgent sundaes -- Retro sundaes -- Grown-up sundaes.
Includes index.
Keywords: ICE CREAM, ICES, ETC